Increasing traditional vegetable consumption in Cavite, Philippines: Understanding consumer and market vendor preferences - Gonzales, Bambi; Chavez, Hidelisa D. de; Sister, Lorna E; Anunciado, Ma. Shiela; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, Danny; Borelli, Teresa; Mendonce, Sharon (2023)
The study conducted in Cavite province sheds light on the factors that influence the availability and accessibility of indigenous vegetables in urban and peri-urban markets. The study specifically looked at the perspectives of both market vendors and consumers in the two primary urban areas of Dasmariñas and Bacoor.